Can allelopathy of Phragmites australis extracts aggravate the effects of salt stress on the seed germination of Suaeda salsa? - Gao, Jingwen; Guan, Bo; Ge, Minjia; Eller, Franziska; Yu, Junbao; Wang, Xuehong; Zuo, Jincheng (Frontiers in Plant Science, 2022)
Phragmites australis is highly adaptable with high competitive ability and is widely distributed in the coastal wetland of the Yellow River Delta. However, allelopathic effects of P. australis on the growth of neighboring plants, such as Suaeda salsa, are poorly understood. In this study, germination responses of S. salsa seeds collected from two different habitats (intertidal zone and inland brackish wetland) to the extracts from different part of P. australis were compared. Potential allelopathic effects on germination percentage, germination rate, radicle length and seedling biomass were analyzed. The germination of S. salsa was effectively inhibited by P. australis extract. Extract organ, extract concentration and salt concentration showed different effects, the inhibitory rates were highest with belowground extract of P. australis between the four different parts. Germination percentage and germination rate were significantly decreased by the interactive effect of salt stress and extract concentration in S. salsa from a brackish wetland but not in S. salsa from the intertidal zone. The impact of different extracts of P. australis on root length and seedling biomass of S. salsa showed significant but inconsistent variation. The response index results showed that the higher concentration of extract solution (50 g L-1) of P. australis had stronger inhibitory effect on the seed germination and seedling growth of S. salsa while the belowground extract had the strongest negative effect. Our results indicated that allelopathy is an important ecological adaptation mechanism for P. australis to maintain a high interspecific competitive advantage in the species’ natural habitat.